MOFs with Open Metal(III) Sites for the Environmental Capture of Polar Volatile Organic Compounds. (28th December 2022) - Severino, Maria Inês; Al Mohtar, Abeer; Vieira Soares, Carla; Freitas, Cátia; Sadovnik, Nicolas; Nandi, Shyamapada; Mouchaham, Georges; Pimenta, Vanessa; Nouar, Farid; Daturi, Marco; Maurin, Guillaume; Pinto, Moisés L.; et al.
Abstract: Metal–Organic Frameworks (MOFs) with open metal sites (OMS) interact strongly with a range of polar gases/vapors. However, under ambient conditions, their selective adsorption is generally impaired due to a high OMS affinity to water. This led previously to the privilege selection of hydrophobic MOFs for the selective capture/detection of volatile organic compounds (VOCs). Herein, we show that this paradigm is challenged by metal(III) polycarboxylates MOFs, bearing a high concentration of OMS, as MIL‐100(Fe), enabling the selective capture of polar VOCs even in the presence of water. With experimental and computational tools, including single‐component gravimetric and dynamic mixture adsorption measurements, in situ infrared (IR) spectroscopy and Density Functional Theory calculations we reveal that this adsorption mechanism involves a direct coordination of the VOC on the OMS, associated with an interaction energy that exceeds that of water. Hence, MOFs with OMS are demonstrated to be of interest for air purification purposes. Abstract : Trimeric metal III) carboxylate Metal‐Organic Frameworks (MOFs) exhibit a preferential adsorption of polar volatile organic compounds (VOCs) over water through a direct binding of the VOC vapor on the open metal sites, paving the way for their utilization in indoor air quality control.